2015
DOI: 10.3109/01443615.2015.1041893
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in pregnancy

Abstract: Thrombocytopenia during pregnancy is quite common. Evaluation of blood counts of pregnant women has shown that thrombocytopenia is the second most common haematological problem in pregnancy, after anaemia. While mostly thrombocytopenia has no consequences for either the mother or the foetus, in some cases it is associated with substantial maternal and/or neonatal morbidity and mortality. It may result from a number of diverse aetiologies. Adequate knowledge of these causes will help the clinicians in making pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
0
12
0
5
Order By: Relevance
“…hypertensive disorders of pregnancy (15-20%), autoimmune processes (3-4%) or secondary to other conditions (1-2%), such as malignancy or infection. 1 ITP is rare in pregnancy, with an incidence of 1/1000 to 1/10,000 pregnancies. 1 Mechanisms behind the triggering or worsening of ITP in pregnancy are unknown, but current hypotheses include the dilutional effect of increased plasma volume and increased platelet turnover.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…hypertensive disorders of pregnancy (15-20%), autoimmune processes (3-4%) or secondary to other conditions (1-2%), such as malignancy or infection. 1 ITP is rare in pregnancy, with an incidence of 1/1000 to 1/10,000 pregnancies. 1 Mechanisms behind the triggering or worsening of ITP in pregnancy are unknown, but current hypotheses include the dilutional effect of increased plasma volume and increased platelet turnover.…”
Section: Discussionmentioning
confidence: 99%
“…1 ITP is rare in pregnancy, with an incidence of 1/1000 to 1/10,000 pregnancies. 1 Mechanisms behind the triggering or worsening of ITP in pregnancy are unknown, but current hypotheses include the dilutional effect of increased plasma volume and increased platelet turnover. 1 Maternal thrombocytopenia increases the risk of spontaneous haemorrhage, especially at platelet counts of under 20 Â 10 9 /l.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palta and Dhiman [ 25 ] have suggested that the investigation of thrombocytopenia is principal to rule out any systemic disorders that may affect pregnancy management as thrombocytopenia can be available as an isolated finding or in combination with underlying situations.…”
Section: Management Of Thrombocytopenia In Obstetric Patientsmentioning
confidence: 99%